The Nepal Earthquake 2015 and its Consequences - Thakur, Rajendra (Academic Voices: A Multidisciplinary Journal, 2018)
Nepal is a hilly country located on the southern lap of Himalayas. Its own identity in the world, Mt. Everest is the highest peak in the world. An earthquake is a major demonstration of the power of the tectonic forces caused by endogenetic thermal conditions of the interior of the earth. It is a natural phenomenon. An earthquake originates at the focus, deep inside the earth, and releases huge energy in the form of waves transmitted through the surface layer of the earth. Movement of the earth itself also creates earthquakes. Earthquakes are hard to predict because we know they will eventually happen just not when. Earthquake can ranges in size from those that are so weak that they cannot be felt to those violent enough to loss people and destroy the whole cities. There are two types of earthquake; Tectonic and volcanic earthquake. In Nepal tectonic earthquake erupted in 25 April and 12 may, 2015 (also known as Gorkha Earthquake), killed nearly 9000 people and injured nearly 22000 people. Its epicenter was east of Gorkha district at Barpak. Due to the eruption of earthquake, hundreds of thousands of people were made homeless with entire villages flattened across many district of the country i. e., Gorkha, Kathmandu, Lalitpur, Bhaktapur, Dhading, Dolkha, Rasuwa and Sindhupalchowk.